2022
DOI: 10.1155/2022/1417752
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Clinical Value of MAGE-A9 Expressions in Cervical Cancer Tissues and PBMC

Abstract: Objective. The aim of this study is to explore the expressions and clinical significance of melanoma-associated antigen-A9 (MAGE-A9) in cervical cancer tissues and peripheral blood mononuclear cells (PBMC). Methods. 108 patients who were scheduled to undergo cervical conization or extensive hysterectomy between March 2019 and January 2021 due to cervical lesions were selected by convenient sampling. According to postoperative pathological results, the patients were divided into a cervical cancer group (n = 64)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%